Pindar's Mythmaking : The Fourth Pythian Ode - Segal, Charles, 1936-2002 (Book collections on Project MUSE., 1986)
Combining historical and philological method with contemporary literary analysis, this study of Pindar's longest and most elaborate victory ode, the Fourth Pythian, traces the underlying mythical patterns, implicit poetics, and processes of mythopoesis that animate his poetry. Originally published in 1986. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.